Approved budget : recurrent and capital estimates of the government of Nasarawa State of Nigeria. - Nassarawa State (Nigeria) ([Lafia, Nigeria : Nasarawa State Govt., 2001)
The document contains the Nasarawa State financial statement for the year 2001. It further highlights sectional and divisional budget estimates allocated to various agencies and ministries, including the executive Governor speech to the honorable members to the house of Assembly.
asm; 11/04/19
Ref
Keywords: Budget; Nassarawa State (Nigeria)